EFFECTIVENESS OF THE PROGRAM FOR HANDLING UNINHABITABLE HOUSES IN SUKABUMI CITY - Siti Robiah; M. Rijal Amirullah; Andi Mulyadi (DIA: Jurnal Administrasi Publik, 2024)
The title of this research is "Effectiveness of The Program for Handling Uninhabitable Houses in Sukabumi City". The purpose of this research is to find out how the Effectiveness of Program for Handling Uninhabitable Houses in Sukabumi City. The background of this research is the uneven distribution of the aid program, the lack of public understanding of the assistance program, and the implementation of this program which is not in accordance with the initial planning of technical implementation guidelines. This research uses a quantitative method with a descriptive approach and data collection techniques using observation techniques, questionnaires, interviews, and documentation. This study uses the theory according to Duncan (1973:274-275) which is influenced by 3 dimensions. The population in this study were people who received assistance in handling uninhabitable houses with a sample of 87 respondents. In analyzing the data, the researcher conducted a validity test, a reliability test, and to test the hypothesis, the researcher used a one-sample t-test. The results of this study indicate that the effectiveness of the program for handling uninhabitable houses is in the very effective category, which means that the effectiveness of the program for handling uninhabitable houses in Sukabumi City has been running very effectively.